Application of Computer Based Technology in College Network English Course. Issue 3 (February 2021) - Yu, Liyan
Abstract: As a carrier of college education, online English course teaching is playing an increasingly prominent role. This paper classifies and compares Web-based English courses from the perspectives of linguistics and cross-cultural communication. To enhance the accuracy of web-based English course teaching application can help students improve relevant knowledge to a certain extent and provide certain help for the development of web-based English courses in colleges and universities. This paper mainly studies the application of network English course from the perspective of computer application theory, so as to provide some help for the research of network English course teaching application.